تقريب النقط الثابتة للتطبيقات شبه المقلصة بوساطة قانون تدريجي جديد (Latakia University Journal -Basic Sciences Series, 2014)
في هذا البحث نقترح صيغة تدريجية جديدة لإيجاد النقط الثابتة لصنف محدد من التطبيقات شبه المقلصة معرفة على مجموعة جزئية محدبة, مغلقة من فضاء Banach, ونبرهن أن تقاربهايكافئ تقارب  كل منالصيغMann ,Ishikaw ,Noor, (5))) نحو نقطة ثابتة للمؤثر شبه المقلص (contractive-Like operator)  . نبرهن أيضاً أن تقارب الصيغة الجديدةأسرع من تقارب)Noor,Ishikawa, (Mann,ولكن تقارب(5) أسرع من تقارب الصيغة الجديدةلهذا النوع من المؤثرات .In this paper, we suggest anew iterative method for finding fixed points of a certain class of quasi-contractive operators defined in a closed, convexsubset of a Banach space. We prove that the convergence of this new iteration is equivalent to the convergence of (Mann,Ishikawa, Noor, (5)) iteration when we use the mapping(contractive-Like operator). Also We prove that the new iteration, is faster than the(Noor , Ishikawa ,Mann) iteration  method but the process (5) is faster than the new process for this class of operators